MATERNAL ANAEMIA AS A RISK FACTOR FOR ADVERSE NEONATAL OUTCOME - Irfan Sarwar1 , Kishwar Ammir2 , Attiya Ayaz 3 , Taj Mohammad4 , Ameer Ali Jamali5 , Resham Baloch6 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT INTRODUCTION: Pregnancy anaemia is a serious health concern and a leading cause of poor feto-maternal outcomes, particularly in underdeveloped countries. Anemia can cause infections, premature rupture of membranes, foetal growth limitation, foetal hypoxia, and other health problems for both the mother and the baby, preterm delivery, low birth weight, increased need for admission to NICU, fetal & neonatal death.OBJECTIVE: To study the association of maternal anemia with adverse neonatal outcome. DETAILS OF THE Research: This was a descriptive, cross-sectional study. SETTINGS: Women and Children Hospital, Abbottabad, Department of Obstetrics and Gynecology. STUDY DURATION: 1 st December 2019 to 10th December 2020. Materials & Methods: A total of 170- women with pregnancy of gestational age >37 weeks, 19 to 40 years of age were included in the study. Patients with diabetes mellitus, Hypertension, CLD, and CRF were not included in the study. Hemoglobin was tested in blood samples taken in Ethylenediaminetetraacetic acid (EDTA) tubes. The degree of maternal anaemia was det ermined, as well as the neonatal prognosis. RESULTS: Maternal anaemia was linked to a greater risk of low birth weight (45.4%), early newborn mortality (13.6%), and increased admission to the neonatal intensive care unit (36.3%) in patients with severe ana emia. The link between mild or moderate anaemia and infant mortality was not significant. SUMMARY: Maternal anaemia raises the risk of low birth weight, premature birth, and perinatal death. Improving maternal nutrition and iron supplements during pregnancy can help to reduce these negative effects.